Unveiling the impacts of humanized birth and obstetric violence from reports of multipare women (Research, Society and Development, 2022)
This work is about the experience reporto f two multiparous women who had one of their births violated and the other in a humanizes way. This research aims to distinguish humanized childbirth from obstetric violence and how they impact the woman’s experience. The main approach used was the semi-structured interview to collect the stories of the two interviewess. After the exploratory field work, the answers were analyzed, grouping the ideas and making them more specific. With this study, it was possible to prove that humanization at the time of childbirth makes a difference, bringing benefits to the mother and newborn, while obstetric violence affects.